2021
DOI: 10.1038/s41598-021-84000-7
|View full text |Cite
|
Sign up to set email alerts
|

A new in vitro model applied 90Y microspheres to study the effects of low dose beta radiation on colorectal cancer cell line in various oxygenation conditions

Abstract: We propose a new in vitro model to assess the impact of 90Y-microspheres derived low-dose beta radiation on colorectal cancer cell line under various oxygenation conditions that mimic the tumor environment. Cancer cells (HCT116) proliferation was assessed using Alamar Blue (AB) assay after 48, 72, and 96 h. FLUKA code assessed changes in cancer cell populations relative to the absorbed dose. In normoxia, mitochondrial activity measured by Alamar Blue after 48–72 h was significantly correlated with the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…It is expected that 90 Y-TARE might also have delayed effects, although this assumption is mainly based on the limitations of traditional imaging techniques in the early assessment of response to 90 Y-TARE. In a recently published in vitro study, in fact, 90 Y-microspheres were found to reduce colorectal cancer cell proliferation as early as within 96 h of observation [ 26 ]. In this perspective, a time interval of 8 weeks after procedure might represent a reasonable gap to assess 90 Y-microsphere effects on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that 90 Y-TARE might also have delayed effects, although this assumption is mainly based on the limitations of traditional imaging techniques in the early assessment of response to 90 Y-TARE. In a recently published in vitro study, in fact, 90 Y-microspheres were found to reduce colorectal cancer cell proliferation as early as within 96 h of observation [ 26 ]. In this perspective, a time interval of 8 weeks after procedure might represent a reasonable gap to assess 90 Y-microsphere effects on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-driven elevation of proangiogenic factors is a hallmark of colorectal cancer and its liver metastasis [ 18 ]. Specifically, in the treatment of colorectal liver metastases, the hypoxic status has also been shown to influence the resistance to antiangiogenic drugs [ 19 ] or their susceptibility regarding radiation therapy, thereby impacting the dosimetric planning for Y-90 radioembolisation [ 20 ]. Moreover, in the era of immune therapies, hypoxia has also been revealed to play a major role in the current understanding of the immune microenvironment of colorectal liver metastases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-driven elevation of proangiogenic factors is a hallmark of colorectal cancer and its liver metastasis [18]. Specifically, in the treatment of colorectal liver metastases, the hypoxic status has also been shown to influence the resistance to antiangiogenic drugs [19] or their susceptibility regarding radiation therapy, thereby impacting the dosimetric planning for Y-90 radioembolisation [20].…”
Section: Introductionmentioning
confidence: 99%